Faktor-Faktor yang Memengaruhi Financial Distress pada Perusahaan Subsektor Makanan dan Minuman - Monica Wulan Martsia Paninggar; Liana Susanto (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to obtain empirical evidence regarding the influence of Return on Assets, Total Assets Turnover, and Intellectual Capital on Financial Distress in food and beverages subsector companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples for this research was 55 companies in the food and beverages subsector which were determined using the purposive sampling method. This observational data was analyzed using multiple linear regression analysis techniques which were processed using IBM SPSS Statistics 27 software. The results of this study show that Return on Assets and Total Assets Turnover have a negative and significant influence on Financial Distress. Meanwhile, Intellectual Capital does not have a significant influence on Financial Distress.